Monitoraggio zootecnico e sanitario di ostriche (Crassostrea gigas) allevate nel Medio Adriatico: risultati preliminari - L. Galosi; A. Roncarati; L. Gennari; F. Tosi; S. Satto; G. Arcangeli; G. E. Magi (SIRAM, 2018)
As part of an Eureka project, 2 batches of cupped oyster (Crassostrea gigas) were monitored paying attention to zootechnical techniques, presence of pathogens (OsHV-1, Vibrio splendidus, Vibrio aestuarianus) and health evaluation of oyster tissues. Rearing techniques were useful to grow the cupper oyster. In both the cycles, the histological examination allowed to observe pathological lesions in oysters sampled in late summer. These displayed atrophic and sometimes necrotic digestive gland with presence of clusters of small rod bacteria attached to the atrophic or necrotic epithelium or free in the lumen. In all the samples was observed within epithelium of gills, mantle and tubules of digestive intracytoplasmic eosinophilic microorganisms, under identification phase. Regarding biomolecular analysis, positive results were found only for the presence of Vibrio splendidus, with high amount in the summer period. Future studies will be necessary to associate the presence of the pathogen with tissue damage and consequent mortality in the cupped oysters raised in the Adriatic Sea. Although not free from production and health problems, it seems that the breeding of cupped oyster in the Middle Adriatic can guarantee good growth performances.